Academia's challenges in the face of the 2022 Russia-Ukraine war - Jaime Teixeira da Silva (European Science Editing)
The European Union (EU), and Europe more widely, is facing its largest socio-political threat in a generation. As the political events between Russia and Ukraine, which have been festering since at least 2014, have now turned into a war, with many major Western and EU companies barring business with Russia, and with most Western Governments imposing increasingly stiffer sanctions on Russia, where do non-Russian academic publishers stand? This commentary takes a brief look at what we know, and where we stand. A humanitarian response is needed, but so too is a decision regarding treatment of Russian and Ukrainian academics.